The role of values in determining graduates' employability and satisfaction of academic programmes - Abdul Rahman, Shukran; Abdul Majid, Hariyati Shahrima; Wok, Saodah; Mohd Noor, Noor Azlan; Mohd Yusof, Danial; Zubairi, Ainol Madziah (Penerbit Universiti Sains Malaysia, 2008)
This study found that higher level of education towards academic programmes in promoting the learning of values accounts for higher level of employability. It was also found that the satisfactory level on the effort to promote the learning of positive values accounts for the level of satisfaction towards academic programmes. The two findings show the significant role of learnt values in predicting graduates' employability and their satisfactory level with the academic programme. The study was based on the cohort of graduates from IIUM's 21st convocation ceremony.